Vehicle fleets path and non-linear ownership elasticity for Bolivia, 2000-2035 - Javier Aliaga Lordemann; Alejandra Terán Orsini (Institute for Advanced Development Studies (INESAD), 2020)
This paper seeks to analyze the evolution of the Bolivian vehicle stock in the mid-term and its policy implications. First, we analyze the relationship between income and vehicle ownership in the country during the period 1970 - 2017 through robust econometric techniques. Based on these results, we use an energy-mix accounting model programmed in General Algebraic Modelling System (GAMS) to analyze how the vehicle fleet and the derived demand of gasoline, natural gas and diesel oil evolved over time. Finally, we observe the trajectory of CO2eq in the transport sector for different types of vehicle categories. Our results prove that the relationship between vehicle ownership and per capita income is highly non-linear and we observe an excessive increase in the vehicle fleet during the last decade. Both of these results will speed up the saturation level of the vehicle fleet in Bolivia. With more equivalented vehicles (EV) on the roads, we expect that the consumption of derivatives will increase over the next years. Hence, we assume imbalances in diesel oil and gasoline production and a lower decarbonization path. Without an energy policy in the transport sector or any energy efficiency measures, the consumption of derivatives would grow 6.9 times and the total emissions of CO2eq would increase 7.93 times in the 2000-2035 period.
Keywords: H23; C25; L62; L9; O3; Q47; Q5; R4; 330; Car ownership; integrated energy-transport modelling; energy-mix; emissions